Bullous Pemphigoid in a Stray Bitch - Gomes Mielezarski, Renata; Pioner de Jesus, Bruna; Faé, Alice; Lopes Simão, Beatriz; de Menezes Teixeira, Elisa; Flores Fernandes, Daniela; Cavalheiro Bertagnolli, Angélica; Carolina Barreto Coelho, Ana (Acta Scientiae Veterinariae, 2024)
Background: Bullous pemphigoid is a sporadic autoimmune skin disease. The clinical manifestations are practically identical to those of the pemphigus complex, with the only difference being the lesion site (subepidermal rather than intraepidermal) and the absence of acantholysis. The cause of this disease remains unclear. This pathology causes ulcerative dermatopathy, which causes vesicles and fragile blisters to develop on the mucocutaneous junctions, plantar region, and mucous membranes. As a differential diagnosis, bullous pemphigoid should be investigated in animals with ulcerative lesions. Therefore, this study reports a case of advanced bullous pemphigoid in a stray bitch. Case: Skin fragments from a 7.8 kg stray bitch of mixed breed and approximately 3 years old were sent to the IPVDF for histopathology. The animal had cachectic lesions on her limb extremities, face, flank, tail, and oral cavity. Because she was a street canine, the condition’s development period is unclear. Skin cytology and fungal culture were performed before the histopathological examination to rule out sporotrichosis. The results were negative, with only one opportunistic fungus identified. Skin cytology showed gram-positive cocci bacteria. A parasitological examination of the skin revealed no mites and a lymph node puncture revealed no significant findings. The ELISA test for leishmaniasis was negative. A complete blood count revealed normochromic normocytic anemia. Biochemical tests (ALT, creatinine, alkaline phosphatase, albumin, urea, and PPT) showed increased ALT. Histopathology revealed mild epidermal hyperplasia, spongiotic foci, dermal inflammatory infiltration, and a subepidermal blister. Initially, the patient was treated with cephalexin and dipyrone, which only helped with the bacterial infection. Itraconazole was used to control the opportunistic fungus. The lesions were treated with zinc oxide ointment, including sunflower oil, vitamin E, and aloe vera. She was also given a bath with benzoyl peroxide. Based on the clinical manifestations, the exclusion of differentials, and the histopathological findings, the diagnosis was bullous pemphigoid. Corticosteroids (Prednisolone) and immunomodulators (Azathioprine) were the definitive treatments that significantly improved the patients. Discussion: Observation of the lesions, complementary tests (to rule out possible diagnoses), and confirmation by histopathological examination (gold standard) led to the diagnosis of bullous pemphigoid. This disease has no sexual or racial predilections in dogs; however, some authors have cited Collies, Shetlands, and Dobermans as breeds vulnerable to developing the disease as young as 5 years old. The animal in the case reported was a mixed breed that appeared to be around 3 years old. Because bullous pemphigoid is a generally serious disease, more aggressive immunosuppressive therapy is necessary. Prednisolone treatment was discontinued after 35 days based on veterinarian guidelines; however, the animal developed ulcerative lesions again. Continuous immunosuppressive treatment is recommended in this case, and other autoimmune diseases are not caused by secondary factors. Histopathological examination, physical examination, and complementary tests were required for diagnosis and treatment. The decisions were successful, and the treatment regimen of corticosteroids and immunosuppressants proved effective in treating bullous pemphigoid. Keywords: autoimmune disease, dermatology, ulcerative lesions, subepidermis, pathology. Título: Penfigoide bolhoso em cadela errante Descritores: dermatologia, doença autoimune, lesões ulcerativas, subepiderme, patologia.